“Parkinson-dementia” diseases: A comparison by double tracer SPECT studies - Rossi, Carlo; Volterrani, Duccio; Nicoletti, Valentina; Manca, Gianpiero; Frosini, Daniela; Kiferle, Lorenzo; Unti, Elisa; De Feo, Paola; Bonuccelli, Ubaldo; Ceravolo, Roberto (Parkinsonism & related disorders, 2009)
We performed 123I-FP-CIT/SPECT and ECD/SPECT in 30 patients with Parkinson's disease with dementia (PDD) and 30 patients with dementia with Lewy bodies (DLB) to evaluate whether presynaptic nigro-striatal function and/or cerebral perfusional pattern is different in these diseases. The striatal uptake of DAT tracer was statistically significantly lower in PDD and DLB with respect to control data ( p < 0.0005), however no significant difference was found between PDD and DLB. Patients with PDD and DLB showed a significant reduction of rCBF ( p < 0.001) in parieto-occipital and frontal areas, with respect to controls, but the comparison between the two groups did not result in any significant difference by SPM analysis. Finally no correlation was found between any regional perfusional changes and nigro-striatal dysfunction. We conclude that neither studies with 123I-FP-CIT nor ECD/SPECT were able to discriminate between DLB and PDD in vivo.